THE EFFECT OF GREEN BETEL LEAF EXTRACT IMMERSION ON NICKEL ION RELEASE IN STAINLESS STEEL ORTHODONTIC BRACKET - Nety Trisnawaty; Aufa Nida Fathiya (Journal of Health and Dental Sciences, 2023)
The orthodontic bracket is an essential component in fixed orthodontic appliances. One of the materials commonly used in orthodontic brackets is stainless steel. Stainless steel orthodontic brackets have good deformation and corrosion resistance. Still, corrosion resistance is compromised by certain conditions in the oral cavity, such as salivary pH due to food and beverage consumption and toothpaste and mouthwash. One of the herbal plants that are widely used for dental and oral health is green betel leaf. Green betel leaves have an acidic pH that may cause corrosion. Corrosion has a detrimental effect on the brackets because it causes a continuous loss of nickel ions. The purpose is to determine the number of nickel ions released from stainless steel orthodontic brackets due to immersion in the green betel leaf extract. This type of research is a laboratory experimental research design with a post-test control group design. The test was carried out on 27 samples divided into three groups. Brackets were immersed in 25% green betel leaf extract, artificial saliva, and a mixture of 25% green betel leaf extract and artificial saliva for 48 hours and measured using an Atomic Absorption Spectrophotome (AAS). The results showed the most significant release of nickel ions occurred in the 25% green betel leaf extract group with a value of 16.37 mg/Kg, and the minor release of nickel ions occurred in the artificial saliva control group with a weight of 1.95 mg/Kg. The conclusion is that green betel leaf extract influences the release of nickel ions in stainless steel orthodontic brackets. DOI : 10.54052/jhds.v3n1.p89-98